Responsible government and responsible business: The challenge of harnessing CSR in a new epoch - Ian Taylor (International Journal of Corporate Social Responsibility (JCSR), 2023)
Much has been written of the implications for government policy on 'responsible business' but a comprehensive review of the subject is needed. This literature review will offer an assessment of varied insights to inform academics and practitioners on an important topic in need of scrutiny. The post-war consensus and strength of collective bargaining is waning in the Western world, and an inflection point may be nearing with a new way of working. Governments leveraging responsible business is among the options, but an understanding of the risks inherent in this option available to society is crucial. The world of business is in a new epoch of accepting social responsibility and, at the same time, a crisis of inequality means there is a need for every element of society to put their shoulder to the wheel. Businesses are an extremely powerful element in society, so how should governments harness that productivity for a social purpose? Should governments be encouraging responsible business to improve living standards and rebalance the inequity of incomes, or should political leaders be wary of engaging well-resourced businesses in areas that should be controlled from a democratic mandate? This article examines responsible business by providing comprehensive coverage of the literature in this deceptively mature subject area. Insights from secondary sources are analysed in relation to four key questions to reach an understanding of the risks inherent in crafting policy that expects more from business. The literature review concludes with a focus on the policy area of education, discussing how responsible business has been put into practice to resolve a market failure identified by J. K. Galbraith in the 1940s. Identifying areas such as this will maximise the opportunity of responsible business.
Keywords: 650; Competitiveness; CSR; Efficiency; Government; Regulatory capture; Responsible business